Pengaruh Sistem Manajemen Keamanan Pangan ISO 22000:2005 Terhadap Kinerja Perusahaan - Dewa Ayu Putu Meitha Candra Dewi; I Wayan Widia; I Gusti Ngurah Apriadi Aviantara (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2017)
Food industries operating in the global market must have a safety management system and international quality standards of food. The aimed of this research was to determine the level of employee satisfaction in the implementation of safety management system and food quality ISO 22000: 2005 towards the performance of PT. Aerofood ACS Denpasar. The implementation of ISO 22000: 2005 was determined using the basic of four key elements, namely the prerequisite programs, HACCP principles, interactive of communication and implementation of resource management system. Meanwhile, the company's performance was determined by the method of Balanced Scorecard. The results showed that 88.56% of employees were satisfied by the implementation of ISO 22000: 2005 and 81.93% were satisfied by the performance of the company. The implementation of ISO 22000:2005 gives positive and significant effect towards company performance. Among the four key elements of the program that were used, it was found that the prerequisite program had the highest impact to improve the performances in terms of financial, customer satisfaction, internal business processes and performance from the perspective of learning and growth. Before PT. Aerofood ACS Denpasar implemented ISO 22000: 2005, it only had cooperation with 7 airlines, but after the success of ISO’s implementation, the number of customers has significantly increased to be 23 airlines.